Halangan Penggunaan Komputer di Kalangan Guru Pendidikan Islam di Daerah Kubang Pasu - Zuraidah, Hj. Abdul Halim (2004)
When the integration of computer technologies in the educational system is increasing the preparedness of teachers to equip themselves in the knowledge of computer use should be taken seriously. The difference of using computer technologies among teachers can be reduces by providing them positive attitudes, aside from giving hem strong support in using computer in the process of teaching and learning. This research seeks to determine the factors which can become the barriers of computer use among the teachers teaching the subject of Islamic Knowledge, in the District of Kubang Pasu. The constrains factor like knowledge, attitudes, facilities, training and motivating, gender difference, length of service and frequency of using computer are studies. The information for this research is gathered through a questionnaire which was distributed to 129 Islamic knowledge teachers in the District of Kubang Pasu, Kedah. The result of this research show that generally, is no significant barriers of computers use among Islamic Knowledge teachers. Pearson Correlation shows that there is significant relationship between variables facilities and motivation. This indicates that the more facilities offered in schools, the motivated teachers will be in using computers. T-test shows there is no significant gender difference. One way ANOVA indicates that there is also no significant difference between the length of service and the barriers in using computers. On the other hand, there are significant differences between attitudes towards and knowledge of computer, with regard to the frequency of computer use. Finally, regression analysis shows that attitudes toward and knowledge of computers are the predictors of frequency of computer use. According to the results of this research, a few suggestions are forwarded to strengthen the positive attitudes that teachers already have toward computer use. Hopefully, the effort will upgrade the Islamic Knowledge through the integration of computer technologies.